2016
DOI: 10.1093/cercor/bhw011
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neural Markers of Flexible Attention over Working Memory in Aging

Abstract: Working memory (WM) declines as we age and, because of its fundamental role in higher order cognition, this can have highly deleterious effects in daily life. We investigated whether older individuals benefit from flexible orienting of attention within WM to mitigate cognitive decline. We measured magnetoencephalography (MEG) in older adults performing a WM precision task with cues during the maintenance period that retroactively predicted the location of the relevant items for performance (retro-cues). WM per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 90 publications
13
64
0
Order By: Relevance
“…Indeed, in sensory areas relevant to the retained perceptual information, α oscillations have since been shown to be attenuated during working memory (e.g., Sauseng et al, 2009; Spitzer and Blankenburg, 2012). Based on the latter work, it has further been hypothesized that the degree of α attenuation during working memory retention may reflect the degree to which the mnemonic representations (which are retained by the underlying neuronal populations) are prioritized (Myers et al, 2014; Poch et al, 2014; Wallis et al, 2015; Mok et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in sensory areas relevant to the retained perceptual information, α oscillations have since been shown to be attenuated during working memory (e.g., Sauseng et al, 2009; Spitzer and Blankenburg, 2012). Based on the latter work, it has further been hypothesized that the degree of α attenuation during working memory retention may reflect the degree to which the mnemonic representations (which are retained by the underlying neuronal populations) are prioritized (Myers et al, 2014; Poch et al, 2014; Wallis et al, 2015; Mok et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…More recently, attenuated α oscillations over task-relevant sensory areas have also been implicated in the retention of perceptual representations in working memory (Jokisch and Jensen, 2007; Sauseng et al, 2009; Spitzer and Blankenburg, 2012). Furthermore, several recent studies have suggested that spatially specific decreases in α oscillations are triggered by orienting attention to an item's spatial location in working memory (e.g., Myers et al, 2014; Poch et al, 2014; Wallis et al, 2015; Mok et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…To date, all of the available evidence on changes in alpha lateralization with age comes from visual studies that contrasted young (~18-30 years) to older (~60-80 years) adults (Sander et al, 2012;Hong et al, 2015;Leenders et al, 2016; but see Mok et al, 2016) while virtually nothing is known about the period where one might suspect age-related change to first surface, that is, middle adulthood (~40-60 years) (Raz, 2005). In light of the well-attested fact that middle-aged adults already show signs of a gradual, if subtle, decline in cognitive abilities and sensory fidelity including hearing (Lin, 2011;Fabiani, 2012), and with new results emerging on the intricate interplay of hearing abilities and maintenance of cognitive fitness Wayne & Johnsrude, 2015;Deal et al, 2016), targeting this age group should be a prime goal for the neuroscience of attention.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is first evidence that distinct attentional mechanisms contribute to the preparation for as opposed to the ongoing processing of a stimulus (van Ede, Szebényi, & Maris, 2014). In addition, we explore whether the proposed mechanistic function of alpha oscillations extends to samples of older participants, which remains an ongoing matter of debate (Hong, Sun, Bengson, Mangun, & Tong, 2015;Mok, Myers, Wallis, & Nobre, 2016;Tune et al, 2018;Vaden, Hutcheson, McCollum, Kentros, & Visscher, 2012).…”
Section: Introductionmentioning
confidence: 98%